What Makes People Feel Close to Online Groups? The Roles of Group Attributes and Group Types - Kraut, Robert E.; Levine, John M.; Escobar, Marisol Martinez; Herdağdelen, Amaç (Proceedings of the International AAAI Conference on Web and Social Media, 2020)
Most research assumes that the determinants of members’ feelings of connection to groups are constant across types of groups. The current paper challenges this assumption by assessing members’ feelings of affinity toward a large, diverse sample of online groups. 10,567 members of 6,458 Facebook groups reported on their feelings of connection to these groups. Objectively measured group characteristics and features of members’ relationship to the groups explained over 16% of the variance in members’ affinity. Being an administrator and being in groups with fewer members, more even communication, and more close friends were the strongest predictors. Half of the independent variables significantly interacted with group type in predicting affinity (e.g., large group size was negatively associated with affinity in task groups and positively associated with affinity in topical groups).